Sport in the modern world and its connection with politics - Kusebaev, Уалихан; Куанышбаева А.А., Куанышбаева А.А. (Рroblems of engineering and professional education, 2022)
In the XXI century sport has become the inalienable part of the politics. The article is devoted to investigation of sport as one of the main resources of the state's «soft power» policy, as an instrument of formation of the country's image. It is studied the experience of South Korea, China, USA, and Russia in the application of «soft power» instruments. It is analyzed the methods of implementation of the «soft power» policy in the field of sport on the example of various countries.